Evaluating a Space-Based Indicator of Surface Ozone-NO(x)-VOC Sensitivity Over Midlatitude Source Regions and Application to Decadal Trends - Jin, Xiaomeng (J Geophys Res Atmos, 2017)
Determining effective strategies for mitigating surface ozone (O(3)) pollution requires knowledge of the relative ambient concentrations of its precursors, NO(x), and VOCs. The space-based tropospheric column ratio of formaldehyde to NO(2) (FNR) has been used as an indicator to identify NO(x)-limited versus NO(x)-saturated O(3) formation regimes. Quantitative use of this indicator ratio is subject to three major uncertainties: (1) the split between NO(x)-limited and NO(x)-saturated conditions may shift in space and time, (2) the ratio of the vertically integrated column may not represent the near-surface environment, and (3) satellite products contain errors. We use the GEOS-Chem global chemical transport model to evaluate the quantitative utility of FNR observed from the Ozone Monitoring Instrument over three northern midlatitude source regions. We find that FNR in the model surface layer is a robust predictor of the simulated near-surface O(3) production regime. Extending this surface-based predictor to a column-based FNR requires accounting for differences in the HCHO and NO(2) vertical profiles. We compare four combinations of two OMI HCHO and NO(2) retrievals with modeled FNR. The spatial and temporal correlations between the modeled and satellite-derived FNR vary with the choice of NO(2) product, while the mean offset depends on the choice of HCHO product. Space-based FNR indicates that the spring transition to NO(x)-limited regimes has shifted at least a month earlier over major cities (e.g., New York, London, and Seoul) between 2005 and 2015. This increase in NO(x) sensitivity implies that NO(x) emission controls will improve O(3) air quality more now than it would have a decade ago.